Dwelling on a Successful Task: Does How or Why Influence Affect?. Issue 3 (16th July 2018) - Flink, Ida K.; Peters, Madelon L.; Bergbom, Sofia; Bergman, Marie; Ekstrand, Karin; Carstens, Johan K.P.; Tillfors, Maria
Repetitive negative thinking (RNT) has been identified as a key maintaining process of emotional difficulties. However, the consequences of repetitive thinking may depend on whether negative thoughts or feelings are processed in an abstract, evaluative mode, or in a concrete, process-focused mode. In recent years an increasing number of studies has also explored the effect of processing mode in relation to positive events, yielding inconsistent results. So far, the studies using positive material have not examined the interaction between trait rumination and processing mode. Consequently, the purpose of this study was to further explore the effects of abstract vs. concrete mode of processing on positive affect and negative affect in the context of a success task in a sample scoring high on trait rumination. 62 participants were randomly assigned to abstract vs. concrete processing training prior to a success task. The results showed that positive affect increased whereas negative affect and state RNT decreased after the success task in both groups. However, abstract vs. concrete processing did not have an effect on outcome. The findings indicate that processing mode does not influence outcome in the context of a success task.